Supine Percutaneous Nephrolithotomy: CON - Alireza Lashay; Erfan Amini; Ali Ahanian; Ardalan Ozhand; Mohammad Masoud Nikkar; Seyed Hossein Hosseini Sharifi (Urology Journal, 2011)
Advocates of supine percutaneous nephrolithotomy (PCNL) consider several theoretical advantages for this procedure. Despite the potential advantages of the supine PCNL, the majority of urologists have remained reluctant to perform this technique. This reluctance may be related to successful outcomes of prone PCNL and technical difficulties associated with supine PCNL. Feasibility of supine PCNL has been shown in different series and the current evidence, although limited and not fully organized, implies the application of this technique for patients with simple stones who are at high anesthesiological risk. However, there is no convincing evidence to support performing supine PCNL in morbidly obese patients and those with complex and multiple stones. Further randomized clinical trials of large sample size and high methodological quality are required to recommend extensive application of supine PCNL as an alternative to prone PCNL.